# Alg 2 - Math

posted by .

need help with hw...

Use Gauss-Jordan to solve

3x – 2y + z = 6

3x + y – z = -4

-x + 2y – 2z = -8

• Alg 2 - Math -

Start by transcribing the equations to a 3x4 matrix
3 -2 1 6
3 1 -1 -4
-1 2 -2 -8
The first step is to reduce each column to zero (except the diagonal element and above) by linear combination of rows. I'll do the first one:
3 -2 1 6
0 3 -2 -10 (row 2 - row 1)
0 4 -5 -18 (3*row 3 + row 1)
Continue:
3 -2 1 6
0 3 -2 -10
0 0 7 14 (4*row 2 - 3*row 3)
The last row can be simplified:
3 -2 1 6
0 3 -2 -10
0 0 1 2
So z=2, substitute z=2 in row 2 to eliminate elements above the diagonal
3 -2 0 4 (row 1 - row 3)
0 3 0 -6 (row 2 + 2*row 3)
0 0 1 2
Simplify row 2:
3 -2 0 4
0 1 0 -2 (row 2/3)
0 0 1 2
Now eliminate column 2 from row 1
3 0 0 0 (row 1 + 2*row 2)
0 1 0 -2
0 0 1 2
So
x=0
y=-2
z=2

## Similar Questions

1. ### Pre-Calculus

Solve for x,y,z, & w using the Gauss-Jordan Elimination Method 5x+3y+z+5w=-2 3x+2y+2z+4w=2 2x+4y+3z-3w=-11 4x-3y-2z+2w=-3 Can anyone help me please?
2. ### math

solve by the gauss-jordan method x+y+z=6 3x+2y-z=4 3x+2y+2z=11
3. ### Algebra

Use the Gauss-Jordan method to invert 1 0 0 2 -1 0 0 0 1 A1= 1 1 1 A2= -1 2 -1 A3= 0 1 1 0 0 1 0 -1 2 1 1 1 can someone help me to invert those matrix using Gauss-Jordan method
4. ### Math

Use the Gauss-Jordan method to solve the equation: 3x-5y-2z=-9 -4x+3y+z=11 8x-5y+4z=6
5. ### Algebra

Use Gauss-Jordan to solve 3x + 2y = -4 4x – 2y = -10
6. ### Algebra

Use Gauss-Jordan to solve 3x + 2y = -4 4x – 2y = -10
7. ### math

how do you solve x+y=2000;6x+8y=14400 using gauss-jordan elimination medthod?
8. ### Math

How do I use gauss-jordan to solve this? Can you explain the steps and show what you multiplied, added, subtracted, etc to each row?
9. ### trig gauss jordan

Write the augmented matrix, and then solve the system, using Gauss Jordan elimination on the augmented matrix. x + 2y - z = 4 -2x + y - 4z = -6 4x - 3y + 2z = -10
10. ### math homework

solve the system by gauss jordan elimination { 1/3x + 3/4 y - 2/3 z = -8 x + 1/2 y - z = -24 1/6 x - 1/8 y - z = -24 a. (-6, 8, -24) b. (-6, -8, -24) c. (0, 8, -24) d. (6, 8, 24) e. (6, -8, 24)

More Similar Questions